A robust NiO–Sm0.2Ce0.8O1.9 anode for direct-methane solid oxide fuel cell. (November 2015) - Tian, Dong; Liu, Wei; Chen, Yonghong; Yu, Weili; Yu, Lianghao; Lin, Bin
Graphical abstract: Highlights: Robust NiO–SDC anode is synthesized by co-assembly for direct-methane SOFC. The cell performance was improved by 40%–45% with the new NiO–SDC anode. No significant degradation of the cell performance was observed after 60 h. The double-pore NiO–SDC anode with higher TPB is promising for SOFC. Abstract: In order to directly use methane without a reforming process, NiO–Sm0.2 Ce0.8 O1.9 (NiO–SDC) nanocomposite anode are successfully synthesized via a one-pot, surfactant-assisted co-assembly approach for direct-methane solid oxide fuel cells. Both NiO with cubic phase and SDC with fluorite phase are obtained at 550 °C. Both NiO nanoparticles and SDC nanoparticles are highly monodispersed in size with nearly spherical shapes. Based on the as-synthesized NiO–SDC, two kinds of single cells with different micro/macro-porous structure are successfully fabricated. As a result, the cell performance was improved by 40%–45% with the new double-pore NiO–SDC anode relative to the cell performance with the conventional NiO–SDC anode due to a wider triple-phase-boundary (TPB) area. In addition, no significant degradation of the cell performance was observed after 60 h, which means an increasing of long term stability. Therefore, the as-synthesized NiO–SDC nanocomposite is a promising anode for direct-methane solid oxide fuel cells.